Demographic, work-related, and life satisfaction predictors of northern social workers' satisfaction with work and profession. (September 2013) - Graham, John R.; Fukuda, Eriko; Shier, Micheal L.; Kline, Theresa J.B.; Brownlee, Keith; Novik, Nuelle
Social workers in northern Canada were surveyed about work and professional satisfaction. Career commitment, turnover, and organizational citizenship predicted organizational satisfaction. Total satisfaction was associated with turnover. Research and theory in social work on remote communities should extend beyond characteristics of work, profession, and environment to include personal life factors.